Modeling and updating the occurrence of Aedes aegypti in its southern limit of distribution in South America - Obholz, Gisella Adriana (2023)
Aedes aegypti is the main vector of arboviruses in the world. This mosquito species is distributed from tropical to temperate regions. In Argentina, it has been reported in 20 out of 23 provinces and reaches its southernmost distribution in the world. Its distribution and persistence are affected by meteorological, demographic and environmental factors, such as temperature, precipitation, and population. The aim of this study was to update and model the occurrence of Aedes aegypti in its southern limit of distribution in Argentina. To this end, a total of 37 sites were inspected in La Pampa and Río Negro provinces. Generalized Linear Models were used to explain the occurrence of Aedes aegypti based on meteorological, environmental and demographic variables. Aedes aegypti was found in 11 cities of La Pampa province where it had not been previously reported, but was not found in any of the cities evaluated in Río Negro province. The averaged model explaining the occurrence of Aedes aegypti included the minimum temperature, precipitation and interactions between maximum temperature and precipitation as explanatory variables. Although precipitation was statistically significant, other factors such as minimum temperature are also important in modeling the occurrence of Aedes aegypti in its southernmost distribution limit.